Development of Mind Meister-Based Learning Media in the Basics of Electronics Engineering Subject at SMK YPM 1 Taman to Improve Learning Motivation - Nizar Sampramudya Yafie; Fendi Achmad; Meini Sondang Sumbawati; Yulia Fransisca (Teknologi Pendidikan ID, 2026)
A decline in student learning motivation persists, largely due to the use of outdated instructional media and teaching models that cause students to become easily bored with the material. To address this issue, the use of website-based instructional media using mind meister platform was proposed as a solution. This study implemented mind meister to assess the extent to which this tool could boost learning motivation in the